SOCIAL MEDIA AS A COMPLEMENTARY SOURCE FOR RELIGIOUS KNOWLEDGE - Latif, Alfa Taufan; Setiawan, Wildan Namora Ichsan (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
Religious content in various formats is served to users on social media and interpreted in many ways. Drawing on interviews with 24 daily social media users, this qualitative study discusses how the audience interprets and utilizes social media content with religious topics. How do users interpret and use social media as a source of religious learning? Especially with their experience of learning about religion before or without the internet. We also discuss their motive to follow religious influencers, accessing content, to the facts about the construction of piousness on their digital presence. This study argues that social media has the potential as not only a place to enjoy religious content but also complementary for learning and moderating the conversation around it. This study also enriches the literature around the intersection of social media and religion.